Shared employment in China: Issues and Challenges / Xiuli Zhao, Mahazril 'Aini Yaacob and Radduan Yusof - Zhao, Xiuli; Yaacob, Mahazril 'Aini; Yusof, Radduan (2021)
Shared employment, which emerged in the fight against the COVID-19, originated from a collaboration between Fresh Hema and Xibei. During the epidemic period, the rapid growth of online orders and delivery services led to the vast labour shortage of Fresh Hema. Xibei was a catering enterprise that was prohibited from serving dine-in meals due to controlling the epidemic. More than 20000 "surplus" employees just filled the labour demand of Fresh Hema, and a new type of "shared employment" mode (also called the shared employees' model) was born (Mo Kaiwei & Li Qingzhi, 2020). Since then, it has been rapidly replicated in different industries. Many companies such as Wal-Mart, Suning, Meituan, SF Express, and Harbin Travel have adopted this new employment model. The application fields have gradually expanded from food delivery and online retail to logistics, manufacturing, and other industries (Arthur Huang & Adam Haney, 2021). It has grown from first-tier cities (most developed areas of the country) to second-and third-tier cities (medium-sized and small cities of the developing world) (Guo Zhengang, 2020). Past studies were only focused on the characteristics, risks, functions, and optimisation paths of shared employment. Little studies were conducted investigating logic generation and systematic analysis of its mode and practice constraints. The initiative was to ensure the protection of legitimate rights and interests of labour. Therefore, the main aim of this article is to explain the shared employment with reference given in China and the issues and challenges faced by the China government about shared employment.